PENGARUH CELEBRITY ENDORSER, BRAND IMAGE DAN KUALITAS PRODUK TERHADAP NIAT BELI SEPEDA MOTOR HONDA VARIO 125 DI KOTA DENPASAR - Kusuma, Made Andi; Santika, I Wayan (E-Jurnal Manajemen, 2017)
The purpose of this study is (1) to determine the effect celebrity endorser influence on purchase intentions Honda Vario 125 in Denpasar, (2) to determine the effect of brand image influence on purchase intentions Honda Vario 125 in Denpasar and (3) to determine the effect of product quality influence on purchase intentions Honda Vario 125 in Denpasar. This research was conducted in Denpasar with data analysis techniques multiple linear regression. The number of samples obtained by using purposive sampling method is a total of 110 respondents. Based on the results of the analysis can be concluded Celebrity endorsers, brand image and product quality and significant positive effect partially on purchase intention Honda Vario 125 in Denpasar. This indicates that the Celebrity endorsers, brand image and product quality may increase purchase intention Honda Vario 125 in Denpasar.
Keywords: celebrity endorser, brand image, quality products, intention buy